THE INFLUENCE OF TRAVEL MOTIVES AND SOCIETY ON SATISFACTION WITH THE DESTINATION AND ACCOMMODATION AT THE DESTINATION - Makuljević, Djordje; Radivojević, NIkola Z (The Business of Tourism, 2023)
The paper examines whether differences in the motives of travel as well as whether differences in society during the trip, as a closely related category with the motive of travel, have an impact on differences in the perception of satisfaction with the destination and accommodation at the destination. The research was conducted on the example of Vrnjačka Banja, as a tourist destination that is experiencing evolution and transformation from a spa destination of mass tourism to a wellness and spa luxury destination, which focuses on bleisure tourists. The research was conducted on a sample of 143 respondents who visited the destination in 2023. Research findings show that differences in travel motives affect satisfaction with the destination, as well as satisfaction with accommodation at the destination. On the other hand, the research did not find clear evidence that differences in society during the trip affect satisfaction with the destination, as well as satisfaction with accommodation at the destination.